Acheta domesticus: A Natural Source of Anti-Skin-Aging Ingredients for Cosmetic Applications - Kankanit Yeerong; Panuwan Chantawannakul; Songyot Anuchapreeda; Thomas Rades; Anette Müllertz; Wantida Chaiyana (MDPI AG, 2024)
Acheta domesticus is an edible insect, rich in nutritional value and considered a sustainable protein source. This study aimed to investigate the potential application of A. domesticus extracts for anti-skin-aging purposes. The extracts were prepared by maceration at ambient temperature with 95% ethanol or hexane and maceration in gentle heat (45 °C) with 95% v/v ethanol or DI water. The extracts were examined for total protein, phenolic, and flavonoid contents. Protein molecular weight distribution was analyzed. The safety of the extracts was investigated in terms of irritation and cytotoxicity. Biological activities relevant to the inhibition of skin aging were evaluated, including increasing transforming growth factor-beta 1 (TGF-β1) expression and inhibitory activities on collagenase and hyaluronidase. The aqueous extract from maceration in gentle heat had the highest total protein content (63 ± 1% w/w), total phenolic content (0.48 ± 0.03 mg GAE/g extract), TGF-β1 stimulating activities (33 ± 2 pg/mL), and collagenase inhibition (with a half maximal inhibitory concentration of 26 ± 1 µg/mL) among various extracts investigated. It caused no irritation to the hen's egg chorioallantoic membrane and showed no cytotoxicity to human dermal fibroblasts and peripheral blood mononuclear cells. Therefore, aqueous A. domesticus extract is proposed as an innovative natural anti-skin-aging ingredient.